H2A.Z.1 crosstalk with H3K56-acetylation controls gliogenesis through the transcription of folate receptor - Su, Libo (Nucleic Acids Res, 2018)
Astrocytes play crucial roles in the central nervous system, and defects in astrocyte function are closely related to many neurological disorders. Studying the mechanism of gliogenesis has important implications for understanding and treating brain diseases. Epigenetic regulations have essential roles during mammalian brain development. Here, we demonstrate that histone H2A.Z.1 is necessary for the specification of multiple neural precursor cells (NPCs) and has specialized functions that regulate gliogenesis. Depletion of H2A.Z.1 suppresses gliogenesis and results in reduced astrocyte differentiation. Additionally, H2A.Z.1 regulates the acetylation of H3K56 (H3K56ac) by cooperating with the chaperone of ASF1a. Furthermore, RNA-seq data indicate that folate receptor 1 (FOLR1) participates in gliogenesis through the JAK–STAT signaling pathway. Taken together, our results demonstrate that H2A.Z.1 is a key regulator of gliogenesis because it interacts with ASF1a to regulate H3K56ac and then directly affects the expression of FOLR1, which acts as a signal-transducing component of the JAK–STAT signaling pathway.